Life cycle assessment of solar‐driven oxidation as a polishing step of secondary‐treated urban effluents. Issue 6 (3rd November 2016) - Ioannou‐Ttofa, Lida; Foteinis, Spyros; Chatzisymeon, Efthalia; Michael‐Kordatou, Irene; Fatta‐Kassinos, Despo
Abstract: BACKGROUND: In this work, the life cycle assessment (LCA) methodology is utilized to estimate the environmental footprint of solar Fenton oxidation at pilot scale used as a polishing step of secondary‐treated urban effluents. All inputs (e.g. natural resources, raw materials, etc.) and outputs (e.g. emissions, etc.) of the process were quantitatively defined and/or estimated. The system under study includes raw materials, energy, land use, chemicals, local transportation needs, and air‐/waterborne emissions. RESULTS: The main environmental hotspots of this system were identified (i.e. energy consumption and use of chemicals). The environmental sustainability of this technology was found to be high, since its environmental footprint for the treatment of 1 m 3 of wastewater was found to be only 8.7 kg CO2 m −3, which is approx. 1.6% of the total CO2 emissions of the treatment of the daily effluents of a Cypriot resident. Nevertheless, alternative scenarios were investigated, in order to further enhance its overall environmental performance. CONCLUSIONS: The results indicate that the majority of the environmental impacts of this process could be attributed to indirect emissions, tracing back to electricity generation, followed by emissions from the chemicals used. The most critical improvement identified herein, is the use of a renewable energy source. © 2016 Society of Chemical Industry